Discourse of University: Knowledge in the Era of Contemporary Forms of Capitalism Development - E. I. Naumova; E. G. Sokolov (Высшее образование в России)
The article represents research in the field of the contemporary forms of economic development based on the knowledge which acts as a new productive force. It is shown that the new stage of economic development is connected to the transformation from the material forms to non-material forms of functioning and has its roots in the cultural revolution of 1970s. The reorganization of the university and the educational organization in European countries in general played the key role as preconditions of the cultural revolution. Marxist methodology was chosen as an instrument for the analysis of knowledge-based economy taking into account the need to develop Marx conception of general intellect (scientific knowledge) and revise the class theory and the theory of surplus value.The key finding is that the contemporary knowledge-based economy implements both financial and productive tendencies in conjunction. It is shown that the predominance of one or another tendency depends on university’s discourse functioning which serves as a mediator between a subject of knowledge and the capitalism discourse. The first tendency reflects undesirable processes of social life: general intellect when it isn’t tied to the production, begins to develop according to the formula «G.I - G.I’», reproducing financial logic of capital increment. In such case, we deal with the process of knowledge submission to capital. The second tendency is connected with the dominance of productive function and defined in terms of cognitive capitalism, where knowledge-based intellectual labor gets its autonomy from capital. Cognitive capitalism represents such form of economic organization where knowledge, as a productive force, makes possible the intellectual productions which involve cognitarians - cognitive workers and producers which are able to create the innovative products. The maintenance and development of the cognitive capitalism become possible in connection with the correct organization of education at university which, in addition to the classic form of knowledge (hard skills), represents a contemporary digital space for the transfer of additional knowledge (soft skills) and serves as a platform for the organization of the effective forms of intellectual productions.